2003
DOI: 10.1051/0004-6361:20030019
|View full text |Cite
|
Sign up to set email alerts
|

Metric observations of transient, quasi-periodic radio emission from the solar corona in association with a “halo” CME and an “EIT wave” event

Abstract: Abstract. We present metric radio observations of quasi-periodic emission from the solar corona in close association with a "halo" CME and an "EIT wave" phenomenon. The radio event lasted for about 60 s. Its mean periodicity was ≈8.8 s. The estimated Alfvén speed in the corona was 1034 km s −1 . The derived height of the source region of the observed quasi-periodic emission, and the magnetic field at the corresponding location (for emission in the fundamental mode) were ∼0.23 R and 6.3 G, respectively. The mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, their spectral characteristics and polarization were not consistent with such interpretation. Thermal emission from CMEs has also been reported at 109 MHz by Kathiravan et al (2002) and Ramesh et al (2003) (Gauribidanur Radioheliograph observations). The thermal free-free CME emission, when detected, can be used for the calculation of the CME mass.…”
Section: Imaging Observations Of Flares and Cmesmentioning
confidence: 71%
“…However, their spectral characteristics and polarization were not consistent with such interpretation. Thermal emission from CMEs has also been reported at 109 MHz by Kathiravan et al (2002) and Ramesh et al (2003) (Gauribidanur Radioheliograph observations). The thermal free-free CME emission, when detected, can be used for the calculation of the CME mass.…”
Section: Imaging Observations Of Flares and Cmesmentioning
confidence: 71%
“…The primary radio bursts associated with coronal waves are metric Type II bursts. It has been noted that the majority of flares of any magnitude range are not necessarily accompanied by Type II activity, implying that an additional condition must be present for the bursts to form (Roberts 1959). With the discovery of Moreton waves (Moreton 1960), it was noticed that there was a strong correlation between metric Type II radio bursts and Moreton waves (Kai 1970).…”
Section: Coronal Bright Fronts and Radio Emissionmentioning
confidence: 99%
“…That both the CMEs and streamers are primarily density enhancements in the solar atmosphere could be a reason for this; 5) for a similar type IVm burst event explained on the basis of optically thin gyro-synchrotron emission from the mildly relativistic non-thermal electrons in the magnetic field of the associated CME core,Tun & Vourlidas (2013) showed that B ≈ 5 − 15 G at r ≈ 1.7 R ⊙ ; 6) type IVm radio bursts associated with the 'leg' of the corresponding CMEs and generated due to second harmonic plasma emission from the enhanced electron density there indicate that B ≈ 4 G at r ≈ 1.6 R ⊙. Considering that the coronal magnetic field associated with the active regions have a range of values(Dulk & McLean 1978;Ramesh et al 2003Ramesh et al , 2011bSasikumar & Ramesh 2013), the different estimates mentioned above can be regarded as reasonable. With measurements of the coronal magnetic field being very limited, particularly in close association with a CME, the results indicate that contemporaneous whitelight and radio observations of the solar corona close to the Sun (r 2 R ⊙ ) are desirable to understand the CMEs and the associated magnetic field.It is a pleasure to thank the staff of the Gauribidanur observatory for their help in observations, maintenance of the antenna and receiver systems there.…”
mentioning
confidence: 99%